Deoxybouvardin-glucoside induces apoptosis in non-small cell lung cancer cells by targeting EGFR/MET and AKT signaling pathway - Na Yeong Lee; Sang Hoon Joo; A-Young Nam; Seung-On Lee; Goo Yoon; Seung-sik Cho; Yung Hyun Choi; Jin Woo Park; Jung-Hyun Shim (EXCLI Journal : Experimental and Clinical Sciences)
Non-small cell lung cancer (NSCLC) is a leading cause of cancer-related deaths worldwide. Its treatment is complicated due to the development of resistance to conventional chemotherapy and targeted therapy. Deoxybouvardin and related cyclic hexapeptides reportedly exhibit antitumor activities, but their mechanisms of action remain unclear. This study aimed to investigate the anticancer mechanisms of deoxybouvardin glucoside (DBG), a glucosidic form of deoxybouvardin from Rubia species, in gefitinib (GEF)-sensitive and -resistant NSCLC HCC827 cells. The effects of DBG treatment on cell proliferation were evaluated using a viability assay. The inhibitory effects of DBG treatment on the activities and phosphorylation of the protein kinases epidermal growth factor receptor (EGFR), MET, and AKTs were assessed using in vitro kinase assay and western blot, respectively. DBG treatment inhibited the growth of HCC827 cells in a concentration- and time-dependent manner. Results of in vitro kinase assay and western blotting showed that DBG treatment significantly inhibited the activities and phosphorylation of the protein kinases EGFR, MET, and AKT. Prediction using molecular docking showed that DBG is located in the ATP-binding pockets of these kinases, supporting the kinase inhibition by DBG treatment. Moreover, DBG treatment induced reactive oxygen species (ROS) generation and cell cycle arrest in the cells. The induction of apoptosis by DBG through caspase activation was confirmed by Z-VAD-FMK treatment. In summary, DBG treatment inhibited the growth of GEF-sensitive and -resistant NSCLC cells by targeting EGFR, MET, and AKTs. Moreover, it induced apoptosis by inducing ROS generation and caspase activation. These results indicate that DBG is a potential therapeutic agent for the treatment of GEF-resistant NSCLC.